Modern day slavery: what drives human trafficking in Europe? - Hernández, Diego; Rudolph, Alexandra (European journal of political economy, 2015)
This paper examines the determinants of human trafficking victim inflows into European countries based on identified victim numbers. We use a gravity-type model to acknowledge data reporting shortcomings. Our empirical results suggest that human trafficking occurs within well-established migrant and refugee corridors and that victims are more likely to be exploited in host countries with weak institutions. Legislation on prostitution activities does not influence victim inflows. Liberalization of border controls intensifies trafficking flows. We find no effect of host countries' acceptance rates of asylum seekers. We conclude that effective policies against human trafficking require sound institutions and a focus on the entire trafficking-chain/channel from source to host countries.